Two‐Phase Exhumation Along Major Shear Zones in the SE Tibetan Plateau in the Late Cenozoic. Issue 8 (23rd August 2018) - Wang, Yang; Zhang, Peizhen; Schoenbohm, Lindsay M.; Zheng, Wenjun; Zhang, Bo; Zhang, Jinjiang; Zheng, Dewen; Zhou, Renjie; Tian, Yuntao
Abstract: Three continent‐scale shear zones are arguably the most outstanding structural features in the southeastern Tibetan Plateau, and therefore, their tectonic and landscape evolution have significant implications for understanding the history and mechanisms of intracontinental mountain building and plateau growth. This study presents low‐temperature thermochronology from the Gaoligong and Chongshan shear zones (GLSZ and CSSZ) and quantitative analyses of fluvial longitudinal profiles of tributaries in the Salween drainage, which lies between the shear zones. Apatite and zircon (U‐Th)/He data reveal a two‐stage exhumation history for both shear zones: rapid and prominent cooling in the middle Miocene followed by a second, lower magnitude cooling event in the late Miocene to early Pliocene. Ductile transpressional shearing is inferred to have caused the first cooling, continuing until ~11 Ma. The northward migration of the tectonic events along the Mogok metamorphic belt and GLSZ and synchronous dextral displacement along the Jiali fault indicate the dominant role of the north advancing eastern Himalayan syntaxis on the surrounding structures. Increased river incision is identified in the middle Salween drainage, leading to two‐segment river profiles and further exhumation along the GLSZ and CSSZ. The tributary transient response could result from temporal changes in uplift or adjustments of the trunk channel to climatic change. Furthermore, glaciers play an important role in shaping the landscape of the upper reaches of catchments in the northern segment of the shear zones. Different drivers for the two exhumation events may reflect distinct stages of plateau growth characterized by different crustal deformation patterns. Key Points: The GLSZ and CSSZ experienced two‐phase exhumation in the late Cenozoic Transpressional shearing caused the first rapid cooling, which continued until ~11 Ma, in response to the northward advance of the EHS Late Miocene‐accelerated incision occurred in the middle Salween drainage due to uplift or climate changes, causing second‐phase exhumation